Georgian Chronicles of Education - Olga Petriashvili (International Society of Philosophy and Cosmology, 2016)
October 24 2015 in Tbilisi, celebrated the 20th anniversary of the Academy of Pedagogical Sciences of Georgia and the presentation of the book "Georgian Chronicles of Education." The origins of Georgian culture, education goes back centuries. In III-VI centuries BC there was a school of rhetoric in Colchis Phasis (now Poti), there were taught rhetoric, literature, astronomy, music, mathematics, basics of philosophy and law. In 326 AD the country adopted Christianity became established Georgian writing. In the IX century Georgia is exempt from the dominion of the United Arab Emirates, and the age of the Georgian Renaissance, marking the success of the economy, culture, education, roads, cities in the country opened two academies: West Georgia - Gelati Academy, in eastern Georgia - Ikalto Academy. In the XIV-XVI centuries as a result of the Mongol invasion of the united Georgian state disintegrated into separate fiefdoms, declined economy and culture. However, since the XVII century, again revived in Georgia education and culture. In the XIX century on the historical arena of Georgia out outstanding Georgian educators: Ilia Chavchavadze, Akaki Tsereteli, Jakob Gogebashvili - the founder of the Georgian national pedagogy, which was first issued for Georgian primary school textbooks:"Mother language the ABC book","The Door to Nature."In 1879 in Georgia it was founded "The Society of spreading Literacy among Georgians." During the Georgian Democratic Republic (1918-1921) was founded by Tbilisi University, opened the Conservatory, the Academy of Arts and other schools. Since independence in 1992, Georgia has focused on Western models of education. In 1995, he founded the Academy of Pedagogical Sciences of Georgia; the president was elected Professor Natela Vasadze. Since 2015 the Academy is headed by Professor David Gotsiridze.